Self‐withdrawal from scheduled bariatric surgery: Qualitative study exploring patient and healthcare provider perspectives. Issue 1 (7th October 2022) - Martin, Mary I.; Ha, Vanessa; Fasola, Laurie; Dalgarno, Nancy; Zevin, Boris
Summary: The objective of the study was to explore the experience of patients who self‐withdrew from their scheduled bariatric surgery (BS) after completing the lengthy multidisciplinary assessment and optimization process, and to examine how these withdrawals affect healthcare providers (HCPs) in a Bariatric Centre of Excellence (BCoE). Interviews were conducted with patients who self‐withdrew, within 1 month, from scheduled BS. Additionally, a focus group with HCPs from the same BCoE was completed. The data were analysed using an inductive, emergent thematic approach with open coding in NVivo 12, with comparative analysis to identify common themes between groups. Eleven patients and 14 HCPs participated. HCPs identified several behavioural and logistical red flags among patients who self‐withdrew from scheduled BS. Patients and HCPs felt the decision was appropriate, owing to a patient's lack of mental preparedness for change, social supports, or fears of postoperative complications. HCPs reported frustration and described negative impacts on clinic efficiency. Additional mental health resources for patients contemplating self‐withdrawal, such as peer support, were suggested. In conclusion, a patient's decision to self‐withdraw from a scheduled BS is often sudden, definite, and associated with anxiety, fear of surgical risks and post‐operative complications. Additional mental health resources at a BCoE may be beneficial to support patients at risk of self‐withdrawal from scheduled BS.